PENGARUH RANGE OF MOTION (ROM) TERHADAP NYERI SENDI PADA LANSIA - Selley Sossa Shahlysa (FKU 15 UMY 583, 2015)
Elderly is a period in which a person will experience a decrease in body functions physically, mentally and socially. Perceived physical deterioration of the elderly one of which is the decline of the movement of the joints. Reduced elasticity of joints will create stiffness in the joints, causing joint pain. ROM is one of the activities that can be used to relieve joint pain that is felt. The purpose of this study tends to investigate the effect of exercise of motion (ROM) of the joint pain that is felt by the elderly. The design of this study with a quasi-experimental pre-post test in the treatment group and the control group. The number of subjects 52 to 26 the treatment group and 26 control group. The treatment group was given motion exercises 3x / week for 6 weeks. Statistical test in the treatment group using a paired sample T-test, the control group using the Wilcoxon signed rank test and comparison test using the Mann Whitney test. Results of research in the treatment group showed that the ROM influential in reducing joint pain elderly (p = 0.000), in the control group did not change significantly (p = 0.265) and there are differences in the effect of a decrease in joint pain in the treatment group and the control group (value p = 0.000)